ANALYSIS OF JARGON USED BY WAITER AT TAMARIND RESTAURANT - Risadi, Nidyantari Laksmi (Samā Jiva Jnānam (International Journal of Social Studies), 2024)
This research focused on identifying and describing the linguistic forms, meanings, and functions of jargon used by waiters in restaurants. Conducted through a qualitative approach, the study explored waiter jargons in both spoken and written formats. The participants were waitstaff from a high-end restaurant. Data collection methods included observation, documentation, and interviews. The findings revealed that the jargon appeared as abbreviations, phrases, and specific terms. The meanings were discerned by examining their technical contexts. Moreover, the study uncovered two main functions of the jargon: (1) providing a specialized language to enhance communication efficiency, and (2) fostering group solidarity. The conclusion drawn from this study is that jargon serves as a means for the community to express their collective identity and maintain their unique linguistic practices.